Organic Crisis, Neoliberalism and Barbarism - Del Roio, Marcos [UNESP] (My University, 2022)
This beginning of the 20s is a milestone in human history. It is a milestone because of the pandemic that devastates the human planet, but even more because of a profound worsening in the structural crisis of capital (Meszaros 2005).